The Utilization Of Artificial Intelligence In The Reactualization Of Pancasila Values Among Generation Z In The Digital Era - Rahma Akbar Ramadhani; Friska Cahya Novianny; Brilian Sangkaeng; Isakhar Isakhar; Louis Louis (Journal of Social Research, 2025)
Generation Z has emerged in an area marked by rapid technological advancement, this condition makes them highly vulnerable to the influence of information that frequently contradicts the fundamental values of Pancasila. The present study seeks to examine the impact of AI ulitization for the recontextualization of Pancasila values, ensuring their continued relevance within the dynamics of the digital age. This research employs a qualitative approach through a comprehensive literature review, focusing on scholarly works related to the use of AI among Generation Z and its implications for the internalizations of national ideology. The findings reveal that AI offers significant opportunities as an effective medium for promoting the learning and dissemination of Pancasila values. At the same time, however, it presents potential risks, particularly the circulation of misinformation and disinformation, which may undermine social cohesion and national unity. These challenges highlight the necessity of adopting strategic measures in AI utilization, including the enhancement of digital literacy, the strengthening of character education, and as well as the formulation of appropriate regulatory frameworks. With such well-directed efforts, AI holds substantial potential to serve as a pivotal instrument in a shaping a golden generation that is not only adaptive to technological change but also firmly anchored in the principles of Pancasila.